Bulk antimony sulfide with excellent cycle stability as next-generation anode for lithium-ion batteries - Yu, Denis Y. W. (2014)
Nanomaterials as anode for lithium-ion batteries (LIB) have gained widespread interest in the research community. However, scaling up and processibility are bottlenecks to further commercialization of these materials. Here, we report that bulk antimony sulfide with a size of 10–20 μm exhibits a high capacity and stable cycling of 800 mAh g−1. Mechanical and chemical stabilities of the electrodes are ensured by an optimal electrode-electrolyte system design, with a polyimide-based binder together with fluoroethylene carbonate in the electrolyte. The polyimide binder accommodates the volume expansion during alloying process and fluoroethylene carbonate suppresses the increase in charge transfer resistance of the electrodes. We observed that particle size is not a major factor affecting the charge-discharge capacities, rate capability and stability of the material. Despite the large particle size, bulk antimony sulfide shows excellent rate performance with a capacity of 580 mAh g−1 at a rate of 2000 mA g−1.